Endophytic Bacteria of Mangrove Roots from the West Coast of Lombok Island with Phosphate-Solubilizing and IAA-Producing Abilities as Biofertilizer Candidates - Zulkifli, Lalu; Sakaroni, Rubiyatna; Rasmi, Dewa Ayu Citra; Wirajagat, Gde Cahyadi (Jurnal Biologi Tropis, 2025)
Mangrove ecosystems are unique habitats with extreme environmental conditions that select for adaptive endophytic microorganisms, making them a potential source of plant growth-promoting bacteria (PGPB). Exploring the potential of endophytes as biofertilizers to reduce dependence on chemical fertilizers is crucial in the context of sustainable agriculture. This study aims to characterize the potential of mangrove root endophytic bacteria from the coast of Lombok as biofertilizer agents through the evaluation of Indole-3-Acetic Acid (IAA) hormone production and phosphate solubilization ability. Endophytic bacteria were isolated from roots, evaluated for IAA production using the Salkowski method, while phosphate solubilization ability was evaluated qualitatively on Pikovskaya agar and quantitatively in liquid culture using molybdenum blue spectrophotometry. Potential isolates were characterized morphologically to determine their bacterial genus. The results showed that all isolates produced IAA, with AV1 (51.52 ppm) and AV4 (42.86 ppm) categorized as high producers. Phosphate solubilization ability varied significantly, with AV1 showing the strongest activity (index 4.41), followed by M1 (1.93), while some isolates showed low to no activity. Quantitative tests showed a peak in dissolved phosphate on day 4, with M2 (18.20 ppm) and M1 (16.31 ppm) being the most efficient phosphate solubilizers. Phenotypic characterization identified all promising isolates (AV1, AV4, M1) as Gram-positive, rod-shaped bacteria belonging to the genus Bacillus sp. based on Bergey’s Manual of Systematic Bacteriology. Overall, AV1, AV4, and M1 were identified as the most promising candidates for further development as biofertilizers.